Rediscovery and redescription of Oxycheila buestani Wiesner with the first female record and new methodology for observation of Oxycheila Dejean and Oxygonia Mannerheim (Coleoptera: Cicindelidae) - Šafránek, Ondřej; Serrano, Verónica Lucía Caballero; Carrasco, Juan Carlos (Zootaxa, 2023)
Biodiversity within the family Cicindelidae (Coleoptera) was studied with respect to ecology in two neighbouring localities on the western slopes of the Andes in central Ecuador. Four different methods were used along two neighbouring streams. One of them, a night vision camera, was successfully used for the first time during the night observation of adults of Oxycheila Dejean, 1825 and Oxygonia Mannerheim, 1837 to record their natural behaviour. The following six species of Cicindelidae were observed together: Oxycheila affinis W. Horn, 1900, Oxycheila pearsoni Wiesner, 1999, Oxycheila brzoskai Wiesner, 1999, Oxycheila buestani Wiesner, 1999, Pseudoxycheila chaudoiri Dokhtouroff, 1882 and Oxygonia oberthueri W. Horn, 1896. The female of the rare Oxycheila buestani is described for the first time here, and the complete redescription of this species, including colour photographs of habitus, habitat and diagnostic characters, is presented.